1981
DOI: 10.2307/1239811
|View full text |Cite
|
Sign up to set email alerts
|

Rural Financial Market Performance: Implications of Low Delinquency Rates

Abstract: In contrast to most developing countries, nonrepayment of agricultural loans has not been a problem for the Costa Rican banking system. Delinquency rates have in fact been lower for agricultural than nonagricultural loans and lowest on loans to small farmers. This good performance is due largely to efficient techniques developed for gathering information about potential borrowers and incentives for borrowers to repay promptly to maintain access to bank loans which carry interest rates substantially below equil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
10
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 4 publications
6
10
0
Order By: Relevance
“…The criteria are favoured based on the argument that low delinquency rate implies that lenders are careful in selecting borrowers and in recovering loans. Vogel (1981), [11] opined that, low rate of loan delinquency suggests that loans are allocated to productive activities. Financial ratios are another tools used in the assessment of financial institutions.…”
Section: Measuring Performance Of Rural Banking Institutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The criteria are favoured based on the argument that low delinquency rate implies that lenders are careful in selecting borrowers and in recovering loans. Vogel (1981), [11] opined that, low rate of loan delinquency suggests that loans are allocated to productive activities. Financial ratios are another tools used in the assessment of financial institutions.…”
Section: Measuring Performance Of Rural Banking Institutionsmentioning
confidence: 99%
“…Experience has shown that no modern developed country around the world achieved rapid industrialization without having previously or simultaneously attained a marked increase in agricultural production (Edordu, 1986). [4] Despite the fact that the nation is blessed with abundant human and natural resources which are favourable for agricultural development, agriculture in Nigeria is dominated by small-scale farmers who are responsible for about 90 percent of the total production (Olatunbode, 1990) [5]. These farmers are characterized by low farm incomes and low technology input.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loan repayment defaults could be reduced by using efficient techniques to gather information about potential borrowers, and by providing incentives to borrowers to meet their repayments promptly, in order to maintain access to bank loans that sometimes attract interest rates below market rates (Vogel, 1986). Vogel observes that low interest rates may cause farmers, and especially small-scale ones, to face severe external capital rationing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, a number of studies reveal that it is farmers who face relatively greater initial obstacles in terms of loan access since agriculture is associated with higher risk exposition (Petrick, 2004;Weber and Musshoff, 2012;Zeller et al, 1998). Simultaneously, empirical findings indicate that farmers do not necessarily default more often (Raghunathan et al, 2011;Vogel, 1981;Weber and Musshoff, 2012); this inevitably contradicts the perception of higher risk.…”
Section: Introductionmentioning
confidence: 99%